PEMBERDAYAAN DESA RAMA AGUNG DALAM PENANGGULANGAN KEMISKINAN EKSTREM DALAM PEREKONOMIAN - Andrea, Regita; Syafri, Fatrica; Sari, Novita; Destianingsih, Rizki; Ahmad Fadila, Yandi; Baida, Faridatul (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
In an economy that is currently increasing, extreme poverty must also be paid attention to in rural areas. Extreme poverty is defined as a condition where people's welfare is below the extreme poverty line, which is equivalent to IDR 17,500 per day. The determination of the extreme poverty line is agreed upon by countries that are members of the UN and the measurement uses an absolute poverty measure that is consistent between countries and over time. We need to know about Rama Agung Village, namely how much influence residence, expenditure and social services have on extreme poverty in the village. Rama the Great. The aim is to find out whether Rama Agung Village is in the extreme poor category or is a Prosperous Village. This research uses descriptive quantitative methods to measure and describe the impact of the empowerment programs implemented on the economic conditions of its citizens. The result is that housing, expenses and social services have a big impact on the high and low levels of extreme poverty in Rama Agung Village.